Analyzing The Use of Taboo Words by Tiktok Influencer - Rakhma Arum Diyanti; Tryas Candra Kurniawan; Rosita Ambarwati (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2024)
Taboo words encompass not only negative and vulgar language, but also words with a positive and sacred connotation that are deemed inappropriate for utterance in any setting. Lately, taboo words are often linked to the era of digital technology, particularly when individuals share their views on events that impact individual and communal situations. The aim of this study is to identify the different categories of taboo language used by TikTok influencers, as outlined in Ronald Wardhaugh's theory. Specifically, these categories include: sex, animal references, religious terms, excretory language, bodily functions, death-related terms, references to mothers-in-law, and terms related to the left hand. The content video was analyzed using a descriptive qualitative approach, in which the investigator described, analyzed, and discussed the data presented in narrative form. The findings revealed four types of prohibited language in the content videos: sex, animal-related terms, elimination, and physical process. It was observed that the most frequently used category in the videos was sex.